Incentives and their relationship to administrative empowerment among the employees of the Department of Scientific, Cultural and Sports Activities at the University of M’sila - تريش لحسن (sports creativity, 2025)
The current study aims to know the correlation between motivation and administrative empowerment among the employees of the Cultural and Sports Activities Department at Mohamed Boudiaf University in M'sila. The researcher used the descriptive approach in the manner of interrelationships, and the questionnaire as a tool for collecting information and data. One of the most important findings is that there is no correlation between material incentives and administrative empowerment, and that there is a weak correlation between moral incentives and administrative empowerment.